PENGARUH STRATEGI DIVERSIFIKASI DAN KEPEMILIKAN MANAJERIAL TERHADAP KINERJA KEUANGAN - Violetta Bella D. Glasius; Marini Purwanto (Media Mahardhika, 2021)
The emergence of the Asean Economic Community (AEC) has an impact on the wider openness of trade between countries so that competition between companies increases. Companies are looking for ways to improve its financial performance so that it can compete among the other competitors. Diversification strategies and managerial ownership can be applied by companies in improving the company's financial performance. Diversification strategy is a strategy that can be used to develop a business, expand market share, and increase competitiveness. Managerial ownership can be used to motivate managerial performance in improving financial performance. This study aims to analyze the effect of diversification strategies and managerial ownership on financial performance. The object this research is using manufacturing companies listed in Indonesia Stock Exchange (IDX) in 2016-2019. This research is a quantitative research with hypothesis testing. The sample used this study were 103 manufacturing companies selected using purposive sampling technique and using multiple linear regression analysis techniques. The results of this study prove that diversification strategy and managerial ownership has no effect on financial performance. The contribution of this research is as additional information regarding the effect of diversification strategies and managerial ownership on financial performance. Limitations of this study is the researchers only collected samples from the official website of the IDX and only use the research object manufacturing company. It is expected that further research can collect data not only on the IDX website but from the company's website and further research is expected to develop a research object.